Notes on the Discovery of a Bronze Age Cemetery, containing Burials with Urns, at Newlands, Langside, Glasgow - Mann, Ludovic McLellan; Bryce, Thomas (Proceedings of the Society of Antiquaries of Scotland, 1905)